The Effect of IFN-γ, Alum and Complete Freund Adjuvant on TNP-KLH Induced Ig.G1, IgE and IgG2a Responses in Mice - R. van Ommen; A. E. C. M. Vredendaal; M. de Gooyer; A. van Oudenaren; H. F. J. Savelkoul (Mediators of Inflammation)
Adjuvants are considered to play an important role in directing the isotype and amount of antibodies produced upon immunization by conducting the development of either Th-1 or Th-2 cells upon T-cell stimulation. This is based on the different cytokine production patterns that were observed after in vitro resttmulation of T cells isolated from mice immunized with antigen either adsorbed on alum or emulsified in complete Freund adjuvant (CFA). However, other studies suggest that primarily the type of antigen determines which isotypes are produced and to what extent. In these studies, however, IgE was not determined. Therefore, this study examined whether alum and CFA influenced the amount and/or ratio of IgG1, IgE and IgG2a produced after TNP-KLH immunization. Similar levels of IgG1, IgE and IgG2a antibodies were found upon immunization with TNP-KLH either adsorbed on alum or emulsified in CFA. Moreover, administration of IFN-γ in combination with TNP-KLH adsorbed on alum did not increase the amount of IgG2a produced. IFN-γ treatment resulted in an increased IL-6 and decreased IFN-γ production by spleen cells upon Con A stimulation, whereas it did not change the IL-4 production in similar conditions. The presented results suggest that upon immunization with TNP-KLH high IL-4 levels are produced, resulting in an antibody response that is dominated by IgG1, independent of the adjuvant employed. The IL-4 inducing property of TNP-KLH is substantiated by the finding that repeated immunization of mice with TNP-KI, without adjuvant, increases the serum total IgE level. The presented data suggest that the carrier part of TNP-KLH preferentially results in Th-2 cell activity after which the adjuvant merely enhances the antibody responses generated.